Vivier reenacted: Singing beyond masculine - Novak, Jelena (New Sound: International Magazine for Music, 2015)
Vivier: A Night Report is a kind of poetical archive of musical details, protocols, experiences, concepts, memories, fears, desires and sorrows connected to Canadian composer Claude Vivier's (1948-1983) unusual destiny. All characters from Marko Nikodijević's opera originate from Vivier's life and works but they are re-indexed, or reenacted differently. The countertenor voice of Vivier is what primarily makes him different from all the rest of the characters. Even it could be claimed that the rest of the voices are dominated by Vivier's vocal presence on stage. Vivier stands as symbol for minority, queer, vulnerable. During his short life he was trying to get his own voice, voice as the personification of freedom and possibility to be heard. Finally he gets vivid, imaginative opera in which both his physical and personified voices are shining by creativity that his art emanate. He gets his singing voice, and he finally gets heard.

La construction sociodiscursive de l'image médiatique de la drag-queen Mado Lamotte. Les frontières de la transgression sociale - Laberge, François (Université Laval, 2013)
Selon la perspective interactionniste de la communication développée par Goffman (1973a, 1973b), l’image qu’un individu a de lui-même et qu’il tente de projeter sur les autres se construit au cours de l’interaction en fonction de représentations socialement partagées. Adoptant cette approche théorique, ma recherche vise à identifier, dans les interventions médiatiques de la drag-queen Mado Lamotte, les procédés discursifs qui participent à la construction de son image publique. L’analyse portera sur les actes de parole potentiellement menaçants (Brown et Levinson, 1987) et à leur amplification (Kerbrat-Orecchioni, 1990). Le corpus est constitué de 29 apparitions télévisées principalement extraites d’émissions de divertissement. La méthode d’analyse du discours (Charaudeau et Maingueneau, 2002) a permis de dégager les différents actes de parole menaçants (Venderveken, 1988) ainsi que les types de procédés par amplification (Vincent, Laforest et Turbide, 2008). L’analyse révèle trois dimensions de transgression sociale dans le modèle de construction de l’image de la drag queen : les normes interactionnelles, la frontière entre les domaines public et privé et l’identité de genre.

"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype